Development Of Electrical Installation Learning Media With Delphi Language - Bagus Dwi Cahyono; Dahliya Sulastri (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Learning Media is a learning tool that is used by someone by using tools that are made to facilitate the delivery of material when teaching at school. Things like that really help teachers in teaching in schools and are a solution to make students happy when learning and not feel bored. One of the learning materials in Vocational High Schools is electrical installation material. Introducing electrical installation material will be very difficult if only with books. Therefore this study aims to adopt material about electrical installations in a computer system. This system is called the Electrical Installation Learning Media in Delphi Language. This system is used to determine the number of light points on an electrical installation from the room size indicator and the amount of lux to be achieved. In addition, the system provides a brief description of the electrical installation material. In this system the electrical installation input data is entered into the computer manually. In building this system, Delphi 7 and Inno Set Up Compiler software are used as installers. The method used in this research is Research and Development (R&D), with the following stages: (1) preliminary research; (2) designing software; (3) collection of materials; (4) initial product development; (5) validation of instructional media experts; (6) product analysis and revision; (8) testing the media in learning; and (9) the final product of the instructional media. The results show that: (1) the results of the feasibility test according to electrical installation experts are that this system is suitable to be used as a learning medium in electrical installation subjects in vocational schools because it contains an explanation of the calculation method of an electrical installation in detail; (2) the results of the feasibility test according to media experts are that this system has very attractive visuals, is user friendly, is compatible with Windows and Linux and the media size is not too large; and (3) the results of the experiment using an indication of the size of the room and the amount of lux to be achieved, obtained data on the number of lamps according to the calculation using the formula.